Initial planting density experiments of narrow-leaved ash in Turkey : ten-year results = Pokusi s početnom gustoćom sadnje poljskog jasena u Turskoj : desetogodišnji rezultati - Özbayram, Ali Kemal (Array, 2020)
Narrow-leaved ash (Fraxinus angustifolia subsp. oxycarpa Vahl.) is a source of valuable wood in Europe and plantations produce high yields in Turkey. Initial planting density plays an important role in plantation silviculture and affects the growth and quality of trees as well as establishment costs. This study aimed to determine the ten-year effects of initial planting density on tree growth and quality of narrow-leaved ash. In 2004, three replications of four initial planting densities (1111, 1667, 2500 and 3333 stem ha–1) were established in a randomized block design in Adapazarı, Turkey. After ten growing seasons, no mortality was seen in all of four planting densities. The initial planting density had no effect on mean stem diameter; however, with the initial planting density increase from 1111 to 3333 stem ha–1, mean tree height was significantly increased and live crown ratio decreased. The H/D ratios at planting densities of 2500 and 3333 stem ha–1 were 21% higher than at lower planting densities. Aboveground dry biomass increased with increasing initial planting density at the stand level, although individual tree sizes were similar. In general, tree form and branch characteristics were improved when initial planting density was increased. Results suggest that on lowland sites where intensive weed competition occurs, higher initial planting density at 2500‒3333 stems ha–1 is recommended for narrow-leaved ash plantations.